Malnutrition infantile à la fin de la période laténienne : l’apport de l’examen paléopathologique de la nécropole de Jort (Calvados, Normandie, France) - Frédéric Boursier; Raphaëlle Lefebvre; Denis Bougault; Cécile Chapelain de Séreville-Niel; Dominique Corde; Vincent Carpentier (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The two archaeological campaigns to excavate the Jort necropolis (Calvados, France), dating to the La Tène D period, revealed a site of exceptional interest for the large number of immature individuals, of which the majority was under five years old. This concentration of immature individuals is unique for this period and region, and as yet there is no obvious explanation accounting for it. The palaeopathological examination of our collection showed a significant recurrence of pathological lesions that are usually associated with deficiency diseases. This population at Jort thus displays a palaeopathological profile potentially indicating a famine situation that could have been related to the serious social instability that characterised the end of the La Tène culture.